Remission of Glucocorticoid-Resistant Polymyalgia Rheumatica achieved with Tocilizumab: 2 Case Reports - Ayse Unal Enginar (Rheumatica Acta: Open Access - Peertechz Publications, 2017)
Polymyalgia rheumatica (PMR) is an idiopathic inflammatory disease characterized by pain and stiffness around the shoulders, neck and hips. IL-6 is an important cytokine in the pathogenesis of the disease. Although glucocorticoids (GC) are the current basic treatment, approximately 50% of patients may experience relapses during treatment. There have been case reports of resistant patients treated with Tocilizumab (TCZ), but as there has been insuffi cient evidence, the 2015 EULAR-ACR did not include TCZ treatment in the PMR recommendations.Two cases of GC-resistant PMR cases where remission was obtained with TCZ treatment are presented in this paper.